Meriem Bennani - life on the CAPS - LaBarge, Emily ca. 20./21.Jh; Wilk, Elvia 1989- (Bidoun, 2023)
A catalog for an exhibition of the latest chapter in Miriem Bennani's CAPS film project. Meriem Bennani is a Moroccan artist who lives and works in New York. Life on the CAPS is the final chapter in her film trilogy of the same name. Set in a supernatural, dystopian future surrounding a fictional island in the middle of the Atlantic Ocean, it is rooted in Bennani's research and reflections on the histories of island societies, biotechnology, and vernacular music. Layering live-action footage and computer-generated animation, Bennani intuitively adapts editing techniques that evoke documentary film, science fiction, phone footage, music videos, and reality TV. Her one-person exhibition at the Renaissance Society marked the debut of this personal, electric yet melancholic consideration of what it is to live in a state of limbo, and this accompanying book captures the film through a combination of still images and selections from a transcript of the film. Enacting a variety of cunning shifts, Life on the CAPS moves fluidly from the imaginary to the geopolitical and ranges from the microscopic scale of DNA to the global eye of surveillance. At the same time, it engages with the power of individual experience as well as the power of collectivity while building on an emotive, formal experimentation that refutes boundaries. This volume includes transcripts of conversations between Meriem Bennani and Omar Berrada, Fatima Al Quadiri and Bidoun, Amal Benzekri, and Aziz Bouyabrine.--University of Chicago Press
Colophon: Published on the occasion of the exhibition "Meriem Bennani: Life on the CAPS". - Exhibition venues: The Renaissance Society at the University of Chicago, February 26 - April 17, 2022; Nottingham Contemporary, May 7 - September 4, 2022; B7L9 Tunis, June 22 - August 20, 2023
Includes bibliographical references
Keywords: Bennani, Meriem / 1988- / Exhibitions; Bennani, Meriem -- 1988-; Film installations (Art) / Exhibitions; Installations filmiques (Art) - Expositions; Exhibition catalogs; Installations filmiques (Art) / Expositions; Ausstellungskatalog -- University of Chicago, Renaissance Society -- 26.02.2022-17.04.2022 -- Chicago, Ill.; Ausstellungskatalog -- Nottingham Contemporary -- 07.05.2022-04.09.2022 -- Nottingham; Ausstellungskatalog -- B7L9 Art Station -- 22.06.2023-20.08.2023 -- Tunis